IMPACT OF MARKET PATRONAGE ON THE TRAFFIC SITUATION IN BENIN METROPOLIS, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
This paper examines the influence of market patronage on the traffic situation in Benin City, Nigeria. Nine market routes were studied, and a well-structured questionnaire administered randomly and systematically was used to collect data from 407 respondents. Descriptive and correlation techniques were used to analyse the responses. Most of the markets were found to be situated along transit routes, and operated every day, resulting in street trading and parking which contributed 76.2 percent to the traffic situation in Benin metropolis. It is suggested that traffic laws prohibiting street trading and parking be enacted and enforced. The marketplaces should be restructured to accommodate motor parks, and alternative routes to bypass market areas for non-market trips should be considered as well as the provision of priority lanes for High Occupancy Vehicles (HOV).
Keywords: Benin City; Congestion; Market patronage; Traffic situation; Transit modes